2016
DOI: 10.1002/2015jc011484
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of seawater pCO2 and sea‐air CO2 fluxes in a fringing coral reef, northern South China Sea

Abstract: Evidence based on four field surveys conducted between July 2009 and April 2011 indicates that both sea surface partial pressures of CO 2 (pCO 2 ) and sea-air CO 2 fluxes at Luhuitou fringing reef in Sanya, Hainan Island, northern South China Sea (SCS) are subject to significant seasonal variations. The diurnal variation of seawater pCO 2 ranges from 264 to 579 latm in summer, which is much larger than that in autumn (152-335 latm), in winter (84-260 latm), and in spring (114-228 latm). The sea-air CO 2 flux i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
4
9
0
Order By: Relevance
“…Our result, however, indicated that the enhanced PP in winter has a stronger influence to draw down the seawater 12 CO 2 than the influx of the DIC with lower δ 13 C values associated with the vertical mixing at our study site. This interpretation is further supported by the field surveys on the coral reef systems in the NSCS, which suggested that the seawater carbonate chemistry of the coral reef was primarily controlled by biological processes (Chen et al, 2015;Dai et al, 2009;Yan et al, 2011Yan et al, , 2016. These results suggest that the decadal variability of the coral Δδ 13 C can be used as a reliable proxy for the PP in the NSCS.…”
Section: The Decadal Variability Of the Primary Productivity Revealedsupporting
confidence: 56%
“…Our result, however, indicated that the enhanced PP in winter has a stronger influence to draw down the seawater 12 CO 2 than the influx of the DIC with lower δ 13 C values associated with the vertical mixing at our study site. This interpretation is further supported by the field surveys on the coral reef systems in the NSCS, which suggested that the seawater carbonate chemistry of the coral reef was primarily controlled by biological processes (Chen et al, 2015;Dai et al, 2009;Yan et al, 2011Yan et al, , 2016. These results suggest that the decadal variability of the coral Δδ 13 C can be used as a reliable proxy for the PP in the NSCS.…”
Section: The Decadal Variability Of the Primary Productivity Revealedsupporting
confidence: 56%
“…The variation in skeletal δ 18 O values of A. gemmifera was consistent with the findings of a previous study demonstrating an enrichment of δ 18 O in the coral skeleton in response to elevated p CO 2 49. The coral calcification rate decreases under reduced pH conditions9, which corresponds to heavier skeletal δ 18 O, whereas low p CO 2 and higher pH lead to species with lighter δ 18 O because HCO 3 − is isotopically heavier than CO 3 2345678910111213141516171819202122232425262728293031323334353637383940414243444546474849. Consequently, the significantly enriched δ 18 O and more depleted δ 13 C in A. gemmifera observed herein may reflect slight reductions in photosynthesis and calcification at the high p CO 2 .…”
Section: Resultssupporting
confidence: 89%
“…Although there is limited evidence for biological adaptation to climate change in coral microbial symbionts, the adaptive power to climate change has been well documented in the photosymbiotic Symbiodinium 101144. The shallow habitat of the coral A. gemmifera sampled in the present study has been experiencing regular large diurnal and seasonal variations in pH/ p CO 2 (see Supplementary Table S1), which are mainly driven by biological activities of the reef282930. Therefore, it is most likely that microbial communities harbored by the natural population of A. gemmifera are resistant to the increased p CO 2 , due to long-term acclimatization/adaptation to the highly dynamic pH conditions within the reef flat.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, a parameterization that includes current velocity and depth, along with wind speed, would be more appropriate for such environments. For previous experiments conducted in coral reef ecosystems shallower than 5 to 10 m (e.g., Cyronak et al, 2014;Frankignoulle et al, 1996;Gattuso et al, 1993;Longhini et al, 2015;Yan et al, 2016), using an ocean wind speed/gas exchange parameterization will likely produce k(600) and CO 2 fluxes that are too low (Table 1).…”
Section: Wind Speed/gas Exchange Parameterizationsmentioning
confidence: 99%